Possibility of a multi-step electroweak phase transition in the two-Higgs doublet models - Aoki, Mayumi; Komatsu, Takatoshi; Shibuya, Hiroto (Progress of theoretical and experimental physics, 2022)
Abstract We discuss whether a multi-step electroweak phase transition (EWPT) occurs in two-Higgs doublet models (2HDMs). The EWPT is related to interesting phenomena such as baryogenesis and the ensuing gravitational wave. We examine parameter regions in CP-conserving 2HDMs and find certain areas where multi-step EWPTs occur. The parameter search shows the multi-step EWPT prefers the scalar potential with the approximate Z2 symmetry and a mass hierarchy between the neutral CP-odd and CP-even extra scalar bosons mA < mH. By contrast, the multi-step EWPT whose first step is strongly first order favors a mass hierarchy mA > mH. In addition, we compute the Higgs trilinear coupling in the parameter region where multi-step EWPTs occur, which can be observed at future colliders. We also discuss a multi-peaked gravitational wave from a multi-step EWPT. Subject index B53, B59